Major Reports of the U.S. Department of Defense - Chapman, Bert (Purdue University, 2017)
Presentation providing an overview of major U.S. Department of Defense reports including the Annual Report on the Military Power of the People's Republic of China, Afghanistan security assessment reports, Arctic Strategy report, Defense Science Board reports, and reports on military retirement and other topics.